2003
DOI: 10.1016/s0928-8244(03)00179-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural antimicrobial susceptibilities and biochemical profiles ofYersinia enterocolitica-like strains:Y. frederiksenii,Y. intermedia,Y. kristenseniiandY. rohdei

Abstract: The natural susceptibility of 131 Yersinia strains of Y. frederiksenii (n=38), Y. intermedia (n=48), Y. kristensenii (n=26) and Y. rohdei (n=19) to 70 antibiotics was tested. Minimum inhibitory concentration (MIC) values were determined with a microdilution procedure in IsoSensitest broth (all strains) and cation-adjusted Mueller Hinton broth (some strains). All species were naturally sensitive or sensitive and of intermediate susceptibility to tetracyclines, aminoglycosides, acylureidopenicillins, numerous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
14
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
6
14
0
Order By: Relevance
“…The majority of the 35 strains isolated from food (74?3 %) were resistant to FOX, as well as AMP, CEF and CFZ. The resistance profile obtained is in agreement with previous studies, in which resistance to AMP and many cephalosporins is frequently observed Tzelepi et al, 1999;White et al, 2002;Stock & Wiedemann, 2003). In fact, the expression of b-lactamase enzymes A and B has already been associated with Y. enterocolitica, Yersinia intermedia and Yersinia frederiksenii (Stock et al, , 2000Tzelepi et al, 1999).…”
supporting
confidence: 91%
“…The majority of the 35 strains isolated from food (74?3 %) were resistant to FOX, as well as AMP, CEF and CFZ. The resistance profile obtained is in agreement with previous studies, in which resistance to AMP and many cephalosporins is frequently observed Tzelepi et al, 1999;White et al, 2002;Stock & Wiedemann, 2003). In fact, the expression of b-lactamase enzymes A and B has already been associated with Y. enterocolitica, Yersinia intermedia and Yersinia frederiksenii (Stock et al, , 2000Tzelepi et al, 1999).…”
supporting
confidence: 91%
“…These susceptibility profiles are similar to those of the type strains Y. intermedia IP3953 and Y. frederiksenii IP6175. They are also similar to the antibiotic susceptibility profiles of Y. intermedia and Y. frederiksenii reported in the literature (2,3,22).…”
Section: Resultssupporting
confidence: 89%
“…For example, organisms not yet shown to produce a functional AmpCtype enzyme but with identified ampC genes include such diverse bacteria as Agrobacterium tumefaciens (110), Coxiella burnetii (GenBank accession number YP_001424134), Legionella pneumophila (56), Rickettsia felis (239), and Sinorhizobium meliloti (127). For other organisms, supportive MIC or enzymatic but not structural data are available for the presence of AmpC ␤-lactamase, including Enterobacter sakazakii (258), Ewingella americana (311), Providencia rettgeri (207), and several species of Serratia (306,307) and Yersinia (215,288,313). The phylum Proteobacteria contains the largest number, but at least one acid-fast actinobacte-rium also produces AmpC ␤-lactamase.…”
Section: Distributionmentioning
confidence: 99%
“…Klebsiella pneumoniae, Klebsiella oxytoca, Proteus mirabilis, and Salmonella spp. (31) lack a chromosomal bla AmpC gene, as do Citrobacter amalonaticus (328), Citrobacter farmeri, Citrobacter gillenii (224), Citrobacter koseri (formerly Citrobacter diversus and Levinea malonatica), Citrobacter rodentium, Citrobacter sedlakii (252), Edwardsiella hoshinae, Edwardsiella ictaluri (312), Kluyvera ascorbata (138,305), Kluyvera cryocrescens (72), Plesiomonas shigelloides (9), Proteus penneri (175), Proteus vulgaris (60), Rahnella aquatilis (30,308), Yersinia pestis, and Yersinia pseudotuberculosis (313) as well as, probably, Escherichia hermannii (91), Francisella tularensis (27), Shewanella algae (123), and Stenotrophomonas maltophilia (111). However, since bla AmpC genes occur on transmissible plasmids, the clinical microbiologist needs to consider this resistance mechanism whatever the identification of an organism.…”
Section: Distributionmentioning
confidence: 99%